2018
DOI: 10.15252/msb.20177733
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐specific responses to the cytokine TGF β are determined by variability in protein levels

Abstract: The cytokine TGFβ provides important information during embryonic development, adult tissue homeostasis, and regeneration. Alterations in the cellular response to TGFβ are involved in severe human diseases. To understand how cells encode the extracellular input and transmit its information to elicit appropriate responses, we acquired quantitative time‐resolved measurements of pathway activation at the single‐cell level. We established dynamic time warping to quantitatively compare signaling dynamics of thousan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(125 citation statements)
references
References 98 publications
8
117
0
Order By: Relevance
“…To determine whether the ligand dose-response is analog (graded response of all cells) or digital (modulation of the fraction of responding cells) we performed stimulation experiments with a range of TGF-β doses (5pM-5nM) and quantified ctgf responses together with SMAD4/2 profiles in single-cells. These experiments revealed a dosedependent (analog) profile of the response characterized by gradually altered SMAD4/2translocation and the target gene activity ( Fig.4A-B), consistent with previous reports 16 . Figure 1C showed clearly defined transients, reaching a peak after 3-4 hours, and then returning to basal levels after around 8 hours ( Fig.5A).…”
Section: Analog Encoding Of Tgf-β Concentration Information By Dose-dsupporting
confidence: 92%
See 2 more Smart Citations
“…To determine whether the ligand dose-response is analog (graded response of all cells) or digital (modulation of the fraction of responding cells) we performed stimulation experiments with a range of TGF-β doses (5pM-5nM) and quantified ctgf responses together with SMAD4/2 profiles in single-cells. These experiments revealed a dosedependent (analog) profile of the response characterized by gradually altered SMAD4/2translocation and the target gene activity ( Fig.4A-B), consistent with previous reports 16 . Figure 1C showed clearly defined transients, reaching a peak after 3-4 hours, and then returning to basal levels after around 8 hours ( Fig.5A).…”
Section: Analog Encoding Of Tgf-β Concentration Information By Dose-dsupporting
confidence: 92%
“…Continuous TGF-β stimulation has been described as generating transient responses, while consecutive pulse stimulations was shown to result in sustained activation 15,17 . This heterogeneity in the response profile of individual cells could be due to differences in negative feedback efficiency 16,27,34 or secondary mechanisms of SMADs recruiting activators and suppressors, thereby shaping the transcriptional response later after stimulation 35 . Surprisingly, we found that SMAD4 but not SMAD2 expression levels regulate the probability of cells to display a transient versus a sustained ctgf transcriptional response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similarity in AMPKAR2 PHOS between daughters decayed gradually, such that it approached the level of unrelated cells with a half-life of ~29 hours. Such patterns of decaying correlation have been observed in other processes, including cell death and signaling pathways (Spencer et al, 2009;Strasen et al, 2018), where they reflect shifts in protein or gene expression complement of each cell that alter cellular phenotype on the scale of 1-2 days (Sigal et al, 2006b).…”
Section: Ampk Responses To Etc Inhibition Reveal Cycling Long-term Mementioning
confidence: 84%
“…As such the observed embedding variability in these rates can be caused by deterministic or stochastic sources [34]. For example, the population context (cell density and morphology) and nonlinear reactions, such as the the cell cycle are deterministic sources of variability [35,36,37,38], while variability in many protein levels is of stochastic nature [32,39,40,41].…”
Section: Discussionmentioning
confidence: 99%